The Impact of CO2 – Induced Warming on Downhill Skiing in the Laurentians - McBoyle, Geoff; Wall, Geoff (Cahiers de géographie du Québec, 1987)
Using the two climatic change scenarios selected by the Canadian Climate Centre, an attempt has been made, using snowcover suitability percentiles, to estimate the resilience and sensitivity of downhill skiing in the Lower Laurentians to the suggested changes in temperature and precipitation. The scenarios suggest an average winter increase in the range of 0 to 16 percent for precipitation and 7.6 to 9.3° F (4.2 to 5.2° C) for temperature. These changes could possibly result in a reduction of the marginally reliable and reliable ski seasons in the Laurentians by 40 to 89 percent respectively with a minimum financial loss of 10$ million and a maximum loss of virtual elimination of the ski industry in this area. It would appear then that downhill skiing in the Lower Laurentians has some resilience to the suggested conditions of one scenario but not the other. In addition, the sensitivity analyses indicate that the ski season length in this part of Canada is little affected until the average winter temperature increases by 4° F (2.2° C).